Late-Onset Carnitine–Acylcarnitine Translocase Deficiency With SLC25A20 c.199-10T>G Variation: Case Report and Pathologic Analysis of Liver Biopsy - Chen, Min; Cai, Yao; Li, Sitao; Xiong, Hui; Liu, Mengxian; Ma, Fei; Xiao, Xin; Hao, Hu (Frontiers in Pediatrics, 2020)
Introduction:Carnitine-acylcarnitine translocase deficiency(CACTD) is a rare and life-threatening autosomal recessive disorder of mitochondrial fatty acid oxidation resulting from variants of the SLC25A20 gene. In Asia, the c.199-10T>G splicing mutation is the most frequently reported. Patients with CACTD with a genotype of c.199-10T>G variation usually presents with a severe clinical phenotype. Case Description: Herein, we report a neonatal case of CACTD identified from Chinese mainland. This patient onset 61 days after birth. She was presented with severe metabolic crisis and her clinical conditions deteriorate rapidly and died of respiratory insufficiency and cardiac arrest 61 days after birth. We present the clinical and biochemical features of this probands and a brief literature review of previously reported CACTD cases with the c.199-10T>G variation. Results: The acylcarnitine profiles by tandem-mass-spectrometry and the high-throughput sequencing confirmed the diagnosis of CACTD in this patient, and homozygous variation of c.199-10T＞G splicing site was found in SLC25A20 gene. In liver pathology, the Prussian blue shows iron deposition in focal hepatocytes, and electron microscopy showed that a large number of lipid droplet vacuoles were observed in the diffuse hepatocytes. Conclusion: We report a CACTD patient who developed disease 61 days after birth, which is the latest onset CACTD patient with c.199-10T＞G variation. Patients with CACTD with a genotype of c.199-10T＞G variation usually presents with a severe clinical phenotype. Early recognition and appropriate treatment is crucial in this highly lethal disorder. Death from late-onset CACTD may be caused not simply by the accumulation of long-chain fatty acids, but also by the effect of iron deposits on heart failure. It is necessary to further study the influence of iron deposition on the pathogenesis of late-onset CACTD, which may increase the treatment of late-onset CACTD.